Dual routes toward observation of a trans-H2/hydride complex in an iridium pincer system and hydrogenation catalytic activity - Agrawal, Nisha K.; Dash, Soumya R.; Vanka, Kumar; Jagirdar, Balaji R. (Organometallics, 2023)
The Abstraction of chloride from a six- coordinate complex, trans-[ Ir(H)(Cl)((iPr)4)(POCOP)(PPh3)] (1) [((iPr)4)(POCOP) = 2,6-bis(di-iso-propylphosphinito)benzene,kappa(3)-C6H3-1,3-[OP(Pr-i)(2 )](2)], using NaBAr4f leads to the generation of a dinitrogen complex, trans-[Ir(H)(N-2)((iPr)4)(POCOP)(PPh3)][BAr4f] (6). Addition of H-2 to [Ir(H)(N-2)((iPr)4)(POCOP)(PPh3)](+) (6) under extremely mild conditions (1 bar, 298 K) resulted in the reversible coordination of H-2 to generate the cis-[Ir(H)(eta H-2-(2))((iPr)4)(POCOP)(PPh3)](+) (cis-11) complex. The cis-[Ir(H)(eta(2)-H-2)((iPr)4)(POCOP)(PPh3)](+) complex (cis-11) isomerized to a trans isomer, trans-[Ir(H)(eta(2)-H-2)((iPr)4)(POCOP)(PPh3)](+) (trans-11), at 253 K. The isomerization process has been studied and supported by computations. Employing an alternative route, protonation of the trans-[Ir(H)(2)((iPr)4)(POCOP)(PPh3)] complex (2) at 183 K resulted in the formation of an identical, trans-[Ir(H)(eta(2)-H-2)((iPr)4)(POCOP)(PPh3)](+) complex (trans-11); upon warming the sample, the trans-H-2/hydride complex isomerized to the cis isomer above 253 K. Two independent routes to obtain trans-[Ir(H)(eta(2)-H-2)((iPr)4)(POCOP)(PPh3)](+) (trans-11) species have been established. Reaction of trans-[Ir(H)(N-2)((iPr)4)(POCOP)(PPh3)][BAr4f] (6) with C2H4 gave the cis-[Ir(H)(eta(2)-C2H4)((iPr)4)(POCOP)(PPh3)](+) complex (cis-15), which also undergoes isomerization to yield an equilibrium mixture of cis/trans-[Ir(H)(eta(2)-C2H4)((iPr)4)(POCOP)(PPh3)](+) complexes (cis-15 and trans-15) at 253 K. The trans-[Ir(H)(N-2)((iPr)4)(POCOP)(PPh3)](+) complex (6) is an excellent catalyst for hydrogenation of ethylene to ethane under very mild conditions.